2019
DOI: 10.3390/sports7090206
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Magnitude and Methods of Rapid Weight Loss Reported by Male Mixed Martial Arts Athletes in Ireland

Abstract: Rapid weight loss (RWL) is frequently practiced in weight category sports, including Mixed Martial Arts (MMA). The aim of the present study was to describe self-reported methods of RWL in a sample of competitive MMA athletes comprising of both amateur and professional fighters. The previously-validated Rapid Weight Loss Questionnaire, with the addition of questions on water loading and hot salt baths, was completed anonymously online by athletes (n = 30; all male, n = 15/15 professional/amateur) from MMA clubs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
48
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(57 citation statements)
references
References 29 publications
4
48
4
1
Order By: Relevance
“…We highlight the fact that there are more sensitive and specific markers to evaluate acute kidney injury than BUN and serum creatinine [ 35 ], given that recent evidence suggest that the BUN-to-creatinine ratio is not a reliable parameter for distinguishing prerenal from intrinsic acute kidney injury [ 36 ]. Our findings did not reveal negative impact on kidney health, contrary to what has been reported in participants that abuse of dehydration methods and diuretics to making weight [ 15 , 37 ], but further research is needed with more sensitive markers and long term monitoring to assess properly the impact of RWL and RWG.…”
Section: Discussioncontrasting
confidence: 99%
“…We highlight the fact that there are more sensitive and specific markers to evaluate acute kidney injury than BUN and serum creatinine [ 35 ], given that recent evidence suggest that the BUN-to-creatinine ratio is not a reliable parameter for distinguishing prerenal from intrinsic acute kidney injury [ 36 ]. Our findings did not reveal negative impact on kidney health, contrary to what has been reported in participants that abuse of dehydration methods and diuretics to making weight [ 15 , 37 ], but further research is needed with more sensitive markers and long term monitoring to assess properly the impact of RWL and RWG.…”
Section: Discussioncontrasting
confidence: 99%
“…It is essential that registered dietitians are involved in this process as they are qualified to advise proper fuelling and weight loss. Similar to previous studies [1,7,9,13,19,24], registered dietitians were found to be an underutilised resource in this group of Silat athletes. Access to registered dietitians for sport-specific weight loss advice is limited as many countries lack sport dietitians.…”
Section: Discussionsupporting
confidence: 87%
“…Further investigation is necessary to discern this. The overall RWLS score of 27.7 ± 8.7 in this group was observed to be lower than Irish MMA fighters (37.9 ± 9.6) [9], Malaysian combat athletes (karate, boxing, taekwondo) (34.7 ± 7.3) [28], Australian combat athletes (boxing, judo, taekwondo, wrestling) (30.6 ± 10.8) [24] and European kickboxers (52.4 ± 12.9) [13]. Although a higher RWLS is indicative of more aggressive weight management, one limitation of the questionnaire is that a linear relationship cannot be assumed between the score and the degree of harm [2].…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations